2018
DOI: 10.3389/fnagi.2018.00200
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term DL-3-n-Butylphthalide Treatment Alleviates Cognitive Impairment Correlate With Improving Synaptic Plasticity in SAMP8 Mice

Abstract: Alzheimer’s disease (AD) is the most prevalent form of dementia worldwide. AD is characterized by mild cognitive impairment at onset, irreversibly progressing with age to severe neurodegeneration and cognitive deficits in the late stages. Unfortunately, no effective treatments exist to prevent or delay the cognitive symptoms of AD. Studies have shown that DL-3-n-butylphthalide (DL-NBP) alleviates cognitive impairment induced by amyloid-β in mice by reducing oxidative stress, inhibiting apoptosis, and decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Studies have demonstrated that NBP exerts multi‐target protective effects against ischemic stroke, including reducing oxidative stress, inhibiting inflammatory responses, alleviating neuronal apoptosis, ameliorating BBB damage, and increasing regional blood flow . Moreover, emerging evidence indicates that NBP also have beneficial effects on cognitive function of Alzheimer's Disease (AD) and vascular dementia, through regulating endoplasmic stress, reducing neuronal apoptosis, and glial reactivity …”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that NBP exerts multi‐target protective effects against ischemic stroke, including reducing oxidative stress, inhibiting inflammatory responses, alleviating neuronal apoptosis, ameliorating BBB damage, and increasing regional blood flow . Moreover, emerging evidence indicates that NBP also have beneficial effects on cognitive function of Alzheimer's Disease (AD) and vascular dementia, through regulating endoplasmic stress, reducing neuronal apoptosis, and glial reactivity …”
Section: Introductionmentioning
confidence: 99%
“…[40] After 3 months of administration of dl-NBP, the levels of SYN and PSD-95 in SAMP 8 mice were significantly elevated. [41] In addition, the brain-derived neurotrophic factor (BNDF)/tropomyosin-related kinase B (TrkB) signaling pathway forms and consolidates memory by regulating synapse formation and plasticity. [41] BNDF and TrkB levels are significantly reduced in SAMP 8 mice, but dl-NBP treatment significantly increases both of the above in SAMP 8 mice.…”
Section: Butylphthalide and Alzheimer Diseasementioning
confidence: 99%
“…[41] In addition, the brain-derived neurotrophic factor (BNDF)/tropomyosin-related kinase B (TrkB) signaling pathway forms and consolidates memory by regulating synapse formation and plasticity. [41] BNDF and TrkB levels are significantly reduced in SAMP 8 mice, but dl-NBP treatment significantly increases both of the above in SAMP 8 mice. [41] Long-term dl-NBP therapy may reduce cognitive decline in SAMP 8 mice by enhancing BDNF/TrkB signaling pathway through the regulation of structural synaptic plasticity.…”
Section: Butylphthalide and Alzheimer Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Dl-3-n-butylphthalide (NBP) belongs to a new class of drugs that protect nerve cells and inhibit apoptosis and is used in the treatment of heart and cerebrovascular diseases (He et al, 2017;Lv et al, 2018). Whether NBP can inhibit PHT-induced apoptosis of nerve cells in the treatment of epilepsy is still unclear.…”
Section: Introductionmentioning
confidence: 99%